Development of Learning Videos Based on Constructivistic Learning Theory on the Theme of 8 Areas I Live in Grade IV Elementary School - Fany Mega Sukma; Arum Ratnaningsih; Suyoto Suyoto (research, training and philanthropy institution Natural Aceh, 2022)
The study reviews the development of learning video media based on constructivist learning theory on the theme of 8 areas where I live in the fourth grade of elementary school. The aims of this research are: (1) Knowing the feasibility of learning videos based on constructivist learning theory on the theme of the 8 areas where I live in grade IV elementary school that was developed, (2) knowing the practicality of learning videos based on constructivist learning theories on the theme 8 areas where I live in class IV school. developed base. This type of research is development research (R&D) with the ADDIE model design consisting of Analysis, Design, Develop, Implementation, and Evaluation. The trial was conducted at SDN Kledungkradenan class IV. This development research resulted: (1) the feasibility of learning videos based on constructivist learning theory got an average score of 3.59 with a very decent category, and (2) the practicality of learning videos based on constructivist learning theory got an average score of 3.75 with the category very practical. Product development in this research can be said to be feasible if it can meet two aspects, namely validity and practicality. a. Validity, whether the developed product is valid or not is obtained from the assessment of experts. The minimum level of product validity is in the range > 2.5 b. Practicality, whether or not the product developed is produced from student response questionnaires. The minimum level of practical value is in the range > 2.5